2007
DOI: 10.1016/j.jcrs.2007.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of corneal endothelium by combined measurement of corneal volume alteration and cell density after phacoemulsification

Abstract: The corneal volume increase after surgery may be indicative of the degree of the endothelial damage in the area; thus, the VSI may be useful in the functional assessment of the corneal endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…The CV increase that occurs following phacoemulsification originates from damage to the corneal endothelial cells [25]. The endothelial cells play a key role in maintaining a non-hydrous state of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The CV increase that occurs following phacoemulsification originates from damage to the corneal endothelial cells [25]. The endothelial cells play a key role in maintaining a non-hydrous state of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Unlike the cell density value, the change in corneal volume, with the 10.0 mm volume in particular, could reflect the total histologic alteration in the cornea, induced not only by endothelial damage but also by mechanical trauma at an incision site. We found little alteration in corneal volume with a lower bottle height, suggesting minimum damage to the entire cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The Scheimpflug camera was used to calculate the corneal volume within 3.0 and 10.0 mm circles in the central cornea. 14,15 Statistical analysis was performed using the unpaired Student t test, F test, 1-way analysis of variance (ANOVA), or Dunnett test, when appropriate.…”
Section: Clinical Studymentioning
confidence: 99%
“…This indicates that the corneal swelling response covers a more substantial corneal region. They further reported that the swelling response from phacoemulsification lasted for three months 7 . Although Doganay and colleagues 8 also used the Pentacam system, they could not reach the same results.…”
Section: Discussionmentioning
confidence: 97%